Serum levels of interleukin-23 and 35 in patients with and without type 2 diabetes mellitus and chronic periodontitis - Avideh Maboudi; Aida Eghbalian; Hajar Seifi; Adele Bahar; Mohadese Heidari; Reza Ali Mohammadpour; Saeid Abediankenari; Seyedeh Leila Poorbaghi; Masood Sepehriamnesh (Babol University of Medical Sciences, 2019)
Background: Type 2 diabetes mellitus (DM) and chronic periodontitis (CP) show common pathophysiological features. We investigated the serum levels of IL-23 and IL-35 in people with type 2 DM and CP. Methods: In a cross-sectional study, 72 patients were divided into four equal groups: group A, participants without type 2 DM and CP; group B, patients with type 2 DM without CP; group C, patients with CP and without type 2 DM; and group D, patients with type 2 DM and CP. Demographic data were obtained and periodontal conditions including clinical attachment loss, bleeding on probing, plaque index, gingival index, and probing depth was evaluated on all existing teeth. Fasting blood sugar (FBS) levels, hemoglobin (Hb) A1c, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were assessed. In addition, serum levels of IL-23 and 35 were measured using enzyme-linked immunosorbent assay. Results: The serum levels of IL-23 and 35 showed no significant differences between all groups (P>0.05). A significant positive correlation between the serum concentration of IL-23 and clinical attachment loss in the control group (r: 0.548, P=0.019) was detected. A significant negative correlation between IL-35 and the plaque index in group B (r: -0.578, P=0.012), plus significant negative correlations between IL-23 with ESR (r: -0.487, P=0.040) and CRP (r: -0.498, P=0.035) in groups C and D were also detected. Conclusion: Despite significant associations of serum concentration of IL-23 and 35 with certain periodontal and inflammatory indices, neither type 2 DM nor CP differentially affects serum levels of these two cytokines.